Natural deep eutectic solvents (NaDES) improves extraction and antioxidant activity of stem bark of Garcinia cowa Roxb. - Fahleni, Fahleni; Mun'im, Abdul; Saputri, Fadlina Chany; Surini, Silvia (Faculty of Pharmacy, Universitas Pancasila, 2025)
Garcinia cowa Roxb. ex DC. is a plant belonging to the Clusiaceae family, and commonly dicovered in Southeast and South Asia. This study aimed to assess the efficiency of eight natural deep eutectic solvents (NaDES) in extracting total xanthones and phenolic compounds from the stem bark using ultrasound-assisted extraction as there is limited research on the use of NaDES in this plant extraction process. The study also examined their antioxidant properties. The NaDES were synthesized with choline chloride and betaine as hydrogen-bond acceptors, accompanied by various acids, alcohols, and glucose as hydrogen-bond donors. In comparison, ethanol was used as standard solvent. The NaDES exhibited higher densities than water, ranging from 1.059 to 1.244 g/cm³, with density increasing according to the number of hydroxyl groups present in the constituents. The total phenolic content (TPC) varied from 22.82 to 28.73 mg GAE/g extract, with NaDES1 (a combination of choline chloride, 1,2-propanediol, and water in a ratio of 1:3:1) showing the highest TPC at 28.73±0.18 mg GAE/g extract. It also exhibited significant antioxidant activities, as demonstrated by DPPH (28.98±0.03 µg/mL) and FRAP assays (43.66±1.51 mmol trolox/g dw). A significant negative correlation was observed between total xanthone, total phenolic content, and IC50 values. These findings suggest that NaDES, particularly NaDES1, have considerable advantages in extracting phenolic compounds and xanthones from G. cowa stem bark, resulting in enhanced antioxidant properties.This highlights the potential of NaDES as eco-friendly and effective solvents for the extraction of bioactive compounds from plant materials.